The Effect Application of the SPEOS Method (Endorphin, Oxytocin, Suggestive Massage Stimulation) with Essential Oil Aromatherapy on Breast Milk Production in Postpartum Mothers - Kadek Widiantari; Ni Made Dewianti; Ni Luh Wayan Adi Arsani (Babali Publisher, 2023)
Background: Breast milk is the primary source of nutrition babies need, where complementary foods have not been recommended for exclusive breastfeeding babies, around 44% worldwide. The low provision of Exclusive Breastfeeding is influenced by a decrease in breast milk production in the first few days after giving birth, so non-pharmacological efforts are needed to increase breast milk production in postpartum mothers, such as the SPEOS method (Stimulation of Endorphin Massage, Oxytocin, and Suggestive) combined with the administration of lavender and fennel essential oil aromatherapy. The purpose of this study is to determine the effectiveness of applying the SPEOS method with lavender and fennel essential oil aromatherapy on increasing breast milk production in postpartum mothers. Method: This research is a quasi-experiment (Quasi Experiment design) with a two-group pre-posttest design. The study was conducted from July to September 2023 with 30 postpartum mothers who met the inclusion criteria with a purposive sampling technique, analysis with a paired t-test, and an independent t-test. Results: There is no significant difference in breast milk production before intervention between the SPEOS group with lavender aromatherapy and the SPEOS group with fennel aromatherapy, with a p-value of 0.66. After intervention, there is no significant difference in breast milk production between the SPEOS group with lavender aromatherapy and the SPEOS group with fennel aromatherapy, with a p-value of 0.28. Conclusion: The SPEOS method with both aromatherapy with lavender aromatherapy and fennel aromatherapy can increase breast milk production.